TRANSFORMASI SOSIAL QUR'ANIK DALAM TAFSIR AL AZHAR - Ach Jamiluddin (UIN Mataram, 2020)
This research proves that Hamka, in Tafsir Al-Azhar, supports the concept of Transformative Islam by : first reunterprenting Islamic theology with interpretations that makes speculative theoretical debates in islmic theology more applicable to arousing human awareness of their role on earth. Second , it supports islam's alignment with social,economic and political conditions and considers it to be as important as the Godhead in Islam. Third, Formulating islamic transformation action through Ta'muruna bi al ma'ruf, tanhawna 'an al-munkar, and tu'minuna billah, but more emphasis on tu' minuna bil Lah.